A Structured ADDIE Approach to Multimedia Learning Development with Lectora Inspire - Bestari, Nyami; Hendra, Robi; Habibi, Akhmad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aimed to develop and evaluate multimedia learning based on the Lectora Inspire application using the ADDIE instructional design model. The research employed a Research and Development (R&D) approach encompassing the stages of analysis, design, development, implementation, and evaluation. The developed multimedia integrated text, images, audio, animations, and interactive quizzes to support secondary school learning. Data were collected through expert validation sheets, teacher practicality questionnaires, student response questionnaires, and a criterion-referenced learning outcomes test administered during a small-group trial. Quantitative data were analyzed using descriptive statistics in the form of percentages and mean scores, while qualitative feedback was used for product refinement. The results show that the multimedia achieved a very high level of validity, with average scores of 92% from media experts, 90% from subject-matter experts, and 88% from teachers. Student responses indicated a high level of engagement, with 89% of students providing positive feedback. Learning outcomes evaluation revealed that most students achieved the predefined mastery criteria after using the multimedia. These findings indicate that Lectora Inspire–based multimedia developed through the ADDIE model is valid, practical, and supportive of learning outcomes achievement. The study contributes to digital pedagogy by presenting a structured and replicable multimedia development framework applicable across subject areas.